Legal strategy to prosper Al Falah Grand Mosque in Sragen Regency from the perspective of Islam and Muhammadiyah - Peggy Dian Septi Nur Angraini; Nur Halimah Widowati; Arya Diandra Diranova Ryanshah (Institute Of computer Science (IOCS), 2026)
The central mosque is a spiritual and social center that shapes the character of the community. However, the prosperity of a mosque does not only depend on physical aspects and implementation, but also on the legal system, Islamic values, and sustainable management strategies. This study analyzes the legal strategies for prospering the Al Falah Grand Mosque in Sragen Regency from the perspectives of Islam and Muhammadiyah. The approach used is descriptive qualitative. The results of the legal strategy to prosper the Al Falah Grand Mosque in Sragen Regency are implemented through mosque management based on Islamic law and positive law regarding waqf and the management of places of worship. The spiritual and social aspects strengthen the congregation's worship activities, Islamic and Muhammadiyah studies, and social services. The modern management aspects include financial transparency, a professional administrative system, and economic empowerment of the community through zakat and productive waqf. The values of Kemuhammadiyahan strengthen the mosque's goal of being a center for progressive da'wah, balancing worship and social roles in the community. The success in prospering the Al Falah Grand Mosque in Sragen Regency is not only in the beauty of the building but also in its ability to integrate legal, spiritual, and humanitarian values. The mosque management model strategy based on Islam and Kemuhammadiyahan can be replicated in other regions.